Development and psychometric properties of an environmental literacy in secondary school - Mujib, Mujib; Mardiyah, Mardiyah; Suherman, Suherman (Revista Fuentes, 2023)
Concurrently, the amount of study into mitigating the effects of environmental issues is growing. Environmental Education is one of the most promising research fields in terms of environmental problem prevention and consequences. However, Nevertheless, environmental literacy is not limited by age, education level, or occupation, especially in the Indonesian context. This study aimed to psychometrically evaluate a secondary education environmental literacy questionnaire. The study sample consisted of 1,021 students in grades 7-9 of junior high schools selected from public and private schools in Indonesia. The validity of the three-factor structure of the model was evaluated using confirmatory factor analysis (CFA), namely environmental consciousness level of 9 items, environmental anxiety level of 6 items, and environmental awareness level of 5 items. Following CFA, fit indices were used to evaluate the model fit. They are as follows: The chi-squared test, comparative fit index (CFI), Tucker-Lewis Index (TLI), Good-Fit Index (GFI), and root mean square approximation error are all examples of test statistics (RMSEA), standardized root mean square residual (SRMR), and KMO index. Reliability values for the three factors ranged between 0.66 and 0.78 with Cronbach Alpha while those for McDonald’s Omega ranged between 0.68 and 0.79. The environmental literacy questionnaire is a feasible instrument to assess junior high school students’ environmental literacy in the Indonesian context.